A new species of Acroneuria (Plecoptera: Perlidae) from Henan Province, China, with redescription of A. hainana Wu, 1938 - Liu, Ruijun; Mo, Raorao; Li, Weihai (Zootaxa, 2019)
A new species of the perlid genus Acroneuria, A. henana sp. nov. from Henan Province of central China is described based on the male, female, and egg. The relationship between the new species and related taxa are discussed. Redescription of male and female of A. hainana Wu, 1938 are also presented.